In vitro evaluation of cytotoxic, anti-proliferative, anti-oxidant, apoptotic, and anti-microbial activities of Cladonia pocillum - Ersoz, M; Coskun, Z. M.; Acikgoz, B.; Karalti, I.; Cobanoglu, G.; Cesal, C. (Cellular and Molecular Biology, 2017)
The aim of this study was to investigate the anti-proliferative, apoptotic, cytotoxic, and anti-oxidant effects of extracts from the lichen Cladonia pocillumon human breast cancer cells (MCF-7), and to characterize the anti-microbial features. MCF-7 cells were treated with methanolic C. pocillum extract for 24h. The cytotoxicity of the extract was tested with MTT. Moreover, its anti-proliferative effects were examined with immunocytochemical method. Apoptosis and biochemical parameters were detected in MCF-7. The methanol and chloroform extracts of the lichen were tested for anti-microbial activity against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans using the disc diffusion method and calculation of minimal inhibitory concentrations. Although BrdU incorporation was not observed in MCF-7 cells treated with methanol extract at a concentration above 0.2 mg/mL, a significant decrease was observed int he percentage of PCNA immunoreactive cells in groups treated with 0.2, 0.4, 06, and 0.8 mg/mL methanol extracts of C.pocillum (49±6.3, 44±5.2, 23±2.5, 0, respectively) compared to that of control (85±4.5). The percentage of apoptotic cells significantly increased in groups treated with 0.2, 0.4, 0.6, and 0.8 mg/mL extracts of the C.pocillum (54±3.5, 76±2.6, 77±1.8, 82±4.2, respectively) compared with that of control group (3.9±1.5).The half-maximal inhibitory concentration of the methanol extract against MCF-7 cells was 0.802 mg/mL .Although the chloroform extract showed more effective anti-microbial activity overall, the methanol extract showed higher anti-fungal activity. Collectively, the results of our study indicate that C.pocillum extracts have strong anti-microbial and apoptotic effects. This lichen therefore shows potential for development as a natural anti-microbial, anti-oxidant, and apoptotic agent.